Kendala Guru Fisika Dalam Menyusun Perangkat Pembelajaran Fisika Berdasarkan Kurikulum 2013 - Wahyuni, Agus; Rezki Putri, Dekla; Susanna; rizal, syamsul (Journal of Technology and Literacy in Education, 2022)
This study aims to determine the constraints of physics teachers in compiling physics learning tools based on the 2013 curriculum in SMAN Se-Kabupaten Aceh Barat Daya. The approach used in this study is a qualitative approach with descriptive research types. Sources of data in this study were all physics teachers at SMAN Se-Kabupaten totaling 28 people. The instruments of data collection used in the study were questionnaires and documentation, which were analyzed using percentages. The results of this study indicate that there are several obstacles experienced by physics teachers in preparing learning implementation plans (RPP), namely constraints in understanding competence by 71%, determining and formulating indicators by 60%, determining learning goals by 60%, determining learning models by 60% , determine the method and approach that corresponds to the characteristics of the material and indicators by 60%, compile the LKPD by 71%, compile the learning process by 79%, and assess the learning process by 60%. From this study it can be concluded that there are obstacles to physics teachers in compiling physics learning tools based on the 2013 curriculum in SMAN Se-Kabupaten Aceh Barat Daya.